Six new cassane diterpenoids from the seeds of Caesalpinia sappan. (June 2016) - Deng, Zhen-Tao; Su, Jia; Ding, Lin-Fen; Tu, Wen-Chao; Yang, Hui; Peng, Li-Yan; Zhao, Qin-Shi; Song, Liu-Dong; Wu, Xing-De
Graphical abstract: Highlights: Six new cassane diterpenoids were isolated from Caesalpinia sappan . 15 known dierpenoids were isolated. Compound 1 is a rare cassane diterpenoid featuring a N bridge between C-19 and C-20. Compounds 1 and 2 exhibited moderate cytotoxicity against three cancer cell lines. Abstract: Six new cassane diterpenoids (1–6 ) and 15 known compounds were isolated and identified from the seeds of Caesalpinia sappan . The structures of the new compounds were determined based on the spectroscopic methods, including 1D and 2D NMR techniques. Compound1 is a rare cassane diterpenoid featuring a nitrogen containing bridge between C-19 and C-20. Compounds1 and2 exhibited moderate cytotoxicity against HCT116, AGS, and HepG2 cell lines with IC50 values ranging from 6.36 to 27.86 μM.